Upcycling Wine Industry Waste: Dealcoholized Grape Pomace as a Platform for Bio-Based Material Innovation - Jorge Miguel Matias; Fernando Braga; Alice Vilela (Applied Sciences)
The wine industry produces substantial amounts of organic waste, particularly in the form of dealcoholized grape pomace—the primary residual biomass that remains after the fermentation process and the extraction of alcohol from winery by-products. This study explores the potential of upcycling dealcoholized pomace, an often-overlooked by-product, into a sustainable platform for innovative bio-based materials. Using a multidisciplinary approach that combines materials science, biotechnology, and principles of the circular economy, we carefully examine the physical, chemical, and mechanical properties of dealcoholized pomace. Our research includes comprehensive analyses of its structural integrity, biodegradability, and potential applications, including biocomposites, eco-friendly packaging solutions, and other sustainable materials. The results of our study highlight not only the promising performance characteristics of dealcoholized pomace, such as its strength-to-weight ratio and biocompatibility, but also underscore its significant role in advancing waste valorization strategies. By effectively transforming waste into valuable resources, we contribute to the development of sustainable materials, thereby supporting a more circular economy within the wine industry and beyond.